PCR detection of Burkholderia cepacia complex as one of key factors to handle a long-term outbreak - Dedeckova, Klara; Fila, Libor; Skalicka, Veronika; Bartosova, Jana; Kucerova, Tereza; Vavrova, Vera; Zemkova, Dana; Kalferstova, Lucie; Melter, Oto; Cinek, Ondrej; Drevinek, Pavel (Journal of cystic fibrosis, 2012)
BACKGROUND: Once the outbreak with Burkholderia cenocepacia ST32 was identified in the Prague cystic fibrosis (CF) centre, molecular tools were implemented into diagnostic routine in order to complement infection control measures with as accurate as possible microbiological service. In addition, genotyping techniques were applied as part of an infection surveillance program to assign species and strain status in samples positive for Burkholderia cepacia complex (Bcc). We sought to evaluate a usefulness of Bcc-specific PCR in infection control and to map evolution of the outbreak. METHODS: Since 2001, 6109 respiratory samples from 299 CF patients were examined not only by conventional culture, but also by PCR, detecting Bcc directly in sputum. RESULTS: Diagnosis of Bcc infection was established by culture in 54 patients already prior to 2001. As 39 more patients were diagnosed by culture and/or PCR during 2001-2010, this represented annual prevalence of 18.5%-28.9%. Twelve of 39 patients were culture negative at the time of their first PCR positivity. Although 2/3 of them became subsequently culture positive, the time delay in diagnostics of the infection by culture ranged from 1 to 22 months. New cases of Bcc infection were detected every year, however a dramatic drop was observed for the epidemic strain ST32. CONCLUSION: A likely factor contributing to the end of ST32 epidemic was segregation of Bcc infected patients that included also patients with no culture, but PCR positivity. The diagnostic PCR led to timely identification of cases with 'culture-invisible' infection.
Keywords: Respiratory Tract Infections; Sputum; polymerázová řetězová reakce; Male; Burkholderia Infections; infekce bakteriemi rodu Burkholderia; techniky typizace bakterií; Česká republika; Burkholderia cepacia complex; Cystic Fibrosis; Adult; sputum; Infection Control; dospělí; Burkholderia cepacia komplex; mužské pohlaví; infekce dýchací soustavy; Czech Republic; kontrola infekce; lidé; cystická fibróza; ženské pohlaví; Humans; epidemický výskyt choroby; Bacterial Typing Techniques; Polymerase Chain Reaction; Disease Outbreaks; Female